One less hope : essays on twentieth-century Russian poets - Ponomareff, Constantin V. (Internationale Forschungen zur allgemeinen und vergleichenden Literaturwissenschaft ;, 2006)
This collection of essays, which should appeal both to Slavists and students of comparative literature, deals with twelve major twentieth-century Russian poets who, for varied reasons, became estranged from the Soviet state. Some stayed in Russia to become inner émigrés, others chose to go into exile in the West. One less hope, one more song (Akhmatova's words), stands both for their suffering and often their deaths, but also for their humanity and poetic achievement. The poets in question are Anna Akhmatova, Osip Mandelshtam, Vladimir Mayakovsky, Alexander Blok, Sergey Esenin, Nikolay Gumilev.